Estimation of gas hydrate and free gas saturation using the rock physics model based on constrained least squares and trust region method in the Shenhu Area, South China Sea - Meng, Dajiang; Zhang, Ruwei; Gu, Yuan; Zhang, Baojin; Lu, Yunqian; Lin, Jiangnan; Wang, Lijie (Frontiers in Earth Science, 2025)
Gas hydrate saturation is a critical parameter for quantitative assessment of hydrate reservoirs. To accurately determine gas hydrate saturation, it is essential to consider various morphological occurrences of hydrates and the coexistence of hydrates with free gas. In this study, we devised a method for estimating the saturations of gas hydrate and free gas as well as the hydrate morphologies by employing the generalized effective medium model based on the constrained least squares and trust region method. Four hydrate occurrence morphologies, namely, contact-cementing, grain-coating, load-bearing, and pore-filling, were integrated into the rock physics model, with the coexistence of hydrates and free gas also being considered. We formulated the inversion as a multi-parameter constrained least squares problem and then used the trust region algorithm to find the optimal least-squares solution. The saturations of gas hydrate and free gas, along with the percentages of hydrate morphologies, were computed using the sonic logs at sites GMGS3-W11 and SH-W01-2017 in the Shenhu Area. The predicted hydrate saturation exhibited comparability to the saturation calculated from resistivity log, NMR log, and chloride data. The gas hydrate saturations predicted for these sites using the rock physics model were found to reach maximum values of 54% and 72%, respectively, while the saturation of free gas could attain up to 22%. The quantitative calculation results of hydrate morphologies reveal that in the Shenhu Area, load-bearing hydrates and pore-filling hydrates predominantly coexist, whereas contact-cementing and grain-coating hydrates are relatively fewer. Additionally, the application results indicate that the trust region algorithm demonstrates favorable global convergence.